Biodiversity and epidemic potential of Chiropteran coronaviruses (Nidovirales: Coronaviridae) - A. M. Shestopalov; Yu. V. Kononova; A. A. Gadzhiev; M. A. Gulyaeva; Marandi Mehdi Vasfi; A. Yu. Alekseev; J. M. Jamalutdinov; M. Yu. Shchelkanov (Юг России: экология, развитие)
Aim. The aim of this review is a comprehensive analysis of current literature data on coronaviruses identified in bats.Discussion. Coronaviruses (Coronaviridae) constitute the most extensive family of viruses of the order Nidovirales. Coronaviruses have a wide range of hosts, including mammals (Alphacoronavirus, Betacoronavirus, Deltacoronavirus, Gammacoronavirus) and birds (Deltacoronavirus, Gammacoronavirus), amphibians (Alphaletovirus) and are pathogens of respiratory, intestinal, cardiovascular. Until the beginning of this century, only etiological agents of mild and moderate respiratory diseases were known among pathogenic coronaviruses for humans. In the 21st century, new highly pathogenic coronaviruses were discovered that caused outbreaks of severe pneumonia with high mortality: the severe acute respiratory syndrome coronavirus (Severe acute respiratory syndrome‐related coronavirus, SARS‐CoV; 2002‐2003, southern provinces of China), the Middle East respiratory coronavirus Syndrome (Middle East respiratory syndrome‐related coronavirus, MERS‐CoV; 2012, western part of Saudi Arabia) and type 2 acute respiratory syndrome coronavirus (Severe acute respiratory syndrome‐related coronavirus 2, SARS‐CoV‐2; 2019 ‐..., the eastern part of central China). The natural reservoirs of SARS‐CoV, SARS‐CoV‐2 and MERS‐CoV are bats (Chiroptera). Coronaviruses circulating in bat populations are not only phylogenetically close to the currently known especially dangerous human viruses but probably have epidemic potential that can be realized in the future.Conclusion. This review presents current data on coronaviruses of bats: taxonomic status, spectrum of potential hosts, distribution. The ecological features of coronaviruses of bats are considered in the context of their epidemiological significance. The origin of pathogenic human coronaviruses is discussed.